2013
DOI: 10.1038/nature12762
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling accretion onto a black hole in the ultraluminous X-ray source M 101 ULX-1

Abstract: There are two proposed explanations for ultraluminous X-ray sources (ULXs) with luminosities in excess of 10(39) erg s(-1). They could be intermediate-mass black holes (more than 100-1,000 solar masses, M sun symbol) radiating at sub-maximal (sub-Eddington) rates, as in Galactic black-hole X-ray binaries but with larger, cooler accretion disks. Alternatively, they could be stellar-mass black holes radiating at Eddington or super-Eddington rates. On its discovery, M 101 ULX-1 had a luminosity of 3 × 10(39) erg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
206
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(219 citation statements)
references
References 43 publications
(73 reference statements)
11
206
1
Order By: Relevance
“…Then, using the constraints on the Eddington luminosity, Middleton et al (2013) estimate a black hole mass of ∼10 M . Also, Liu et al (2013) confirm a probable Wolf-Rayet companion star to a supersoft ULX in M101. They use this to calculate a mass function, and find that it likely contains an ∼20-30 M black hole.…”
Section: Introductionmentioning
confidence: 62%
“…Then, using the constraints on the Eddington luminosity, Middleton et al (2013) estimate a black hole mass of ∼10 M . Also, Liu et al (2013) confirm a probable Wolf-Rayet companion star to a supersoft ULX in M101. They use this to calculate a mass function, and find that it likely contains an ∼20-30 M black hole.…”
Section: Introductionmentioning
confidence: 62%
“…Gilfanov et al 2004, Luangtip et al 2014 continues to this day as new observations arise, and the balance has tipped recently in favour of stellar-mass BHs and NSs (M101 ULX-1, Liu et al 2013;NGC7793 P13, Motch et al 2014;M-82 X-2, Bachetti et al 2014) rather than IMBHs. It is actually interesting that the observations do not favour the "simpler" resolution of this issue: the main difficulty with ULXs is that they should not radiate above the Eddington limit (L Edd = 1.3 × 10 38 (MX /M ) erg s −1 ), and IMBHs with masses MX ∼10 2−4 M would remain comfortably below this limit.…”
Section: Discussionmentioning
confidence: 99%
“…Another class of objects thought to contain stellar-mass BHs are the ULX sources (Liu et al 2013, Motch et al 2014. Their X-ray luminosities (10 39 −10 41 erg s −1 ) exceed the Eddington limit for a NS by 1 − 3 orders of magnitude.…”
Section: High-mass X-ray Binariesmentioning
confidence: 99%
“…It is suggested that ULXs are also powered by accretion onto stellar-mass black holes (< 100M⊙) at or in excess of the ⋆ E-mail: cpinto@ast.cam.ac.uk Eddington limit (e.g. King et al 2001, Poutanen et al 2007, Gladstone et al 2009, Liu et al 2013 or accretion at more sedate Eddington ratios onto intermediate mass black holes (10 3−5 M⊙, e.g. Greene and Ho 2007, Farrell et al 2009, Webb at al.…”
Section: Introductionmentioning
confidence: 99%